Estrategias de comunicación que se usan en las escuelas de fútbol de niños de la ciudad de Ibarra - Malquin Castro, Ronny Alexander (2023)
The current research addresses the problem of the lack of communication strategies in children's soccer schools in the city of Ibarra and how this has a direct impact on relations with the target audience, corporate image and brand positioning of these entities. The main objective of the research is to analyze the communication strategies applied in these schools through an experimental study. For this purpose, a mixed research approach was applied, combining quantitative and qualitative techniques. In-depth interviews were conducted with the owners responsible for communication in the soccer schools and with experts in sports communication from professional teams in the country. Likewise, a survey was conducted with parents and representatives of the children belonging to the schools, in order to collect data on their perception and level of satisfaction with respect to the communication strategies implemented. The results revealed the absence of a communicator or specialized team in charge of implementing communication strategies in the children's soccer schools. Instead, the owners themselves assume this function in an empirical manner, without a previous study or adequate planning. However, in spite of this inadequacy, parents showed a positive response to these strategies that have been employed so far. The applied thesis emphasizes the importance of having professionals specialized in the area of communication for the development of effective strategies in children's soccer schools. This will allow improving relations with their target, strengthening the corporate image of the different institutions and thus achieving a better brand positioning. In addition, the importance of planning and carrying out previous studies on communication strategies to maximize results and exceed the expectations of parents and representatives is highlighted.